The pricing of initial public offering and market efficiency - CHIRAPHOL, Chiyachantana N. (Institutional Knowledge at Singapore Management University, 2021)
This study investigates long-run performance of Thai initial public offerings (IPOs). To examine the longrun performance of Thai IPOs, we compute buy-and-hold abnormal returns and cumulative abnormal returns for two years after the IPOs. We find strong evidence of long run underpricing in Thai market. Specifically, the average buy-and-hold abnormal returns and cumulative abnormal returns are 64.5% and 18.4% respectively. However, our multi-variate analysis does not indicate a strong relation between long-run underperformance and firm-specific factors, such as firm size, firm age, investment banker reputation and firm profitability.